2021
DOI: 10.15294/eeaj.v10i3.46907
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, Financial Literacy, and Financial Behavior of Women Working in Manufacturing Industry

Abstract: The purpose of this study is to determine the effect of demographic factors and financial literacy on financial behavior of women working in manufacturing industry. Women are the targets of financial literacy due to their involvement in fulfilling the household needs and welfare. This research is quantitative research. Using the questionnaire on 115 respondents in this study from various manufacturing industries in Purbalingga with probability sampling as the technique. While the data analysis technique used S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
3
6
0
Order By: Relevance
“…These research findings are consistent with studies conducted by (Arofah, 2019;Hidayat & Paramita, 2022;Humaidi, Khoirudin, Adinda, & Kautsar, 2020;Mutlu & Ozer, 2022;Panjaitan & Digdowiseiso, 2023;Pratama, Jasman, & Saharudin, 2022;Rohmanto & Susanti, 2021;Sukma & Pradana, 2022;Wahyudi, Tukan, & Pinem, 2020;Wiranti, Goso, & Halim, 2023) stating that financial literacy has a positive and significant influence on financial behavior.…”
Section: Discussion the Influence Of Financial Literacy (X1) On Finan...supporting
confidence: 90%
See 2 more Smart Citations
“…These research findings are consistent with studies conducted by (Arofah, 2019;Hidayat & Paramita, 2022;Humaidi, Khoirudin, Adinda, & Kautsar, 2020;Mutlu & Ozer, 2022;Panjaitan & Digdowiseiso, 2023;Pratama, Jasman, & Saharudin, 2022;Rohmanto & Susanti, 2021;Sukma & Pradana, 2022;Wahyudi, Tukan, & Pinem, 2020;Wiranti, Goso, & Halim, 2023) stating that financial literacy has a positive and significant influence on financial behavior.…”
Section: Discussion the Influence Of Financial Literacy (X1) On Finan...supporting
confidence: 90%
“…Research conducted by (Arofah, 2019;Hidayat & Paramita, 2022;Humaidi, Khoirudin, Adinda, & Kautsar, 2020;Mutlu & Ozer, 2022;Panjaitan & Digdowiseiso, 2023;Pratama, Jasman, & Saharudin, 2022;Rohmanto & Susanti, 2021;Sukma & Pradana, 2022;Wahyudi, Tukan, & Pinem, 2020;Wiranti, Goso, & Halim, 2023) support the statement that financial literacy has a positive and significant effect on financial behavior. H1: Financial literacy positively and significantly affects the financial behavior of students who use online shopping platforms.…”
Section: Financial Literacymentioning
confidence: 94%
See 1 more Smart Citation
“…In a study with undergraduate students comprising the sample, Arofah (2019) found that a high level of self-efficacy is associated with more effective financial management. Other studies in a similar vein in reference specifically to financial self-efficacy and financial management affirm that the extent of a person's selfefficacy has a determinative relationship with the effectiveness of his/her financial behavior (Danes and Haberman, 2007;Farrell et al, 2016).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Financial selfefficacy is one aspect developed from the theory of self-efficacy about positive beliefs in the ability to successfully manage personal finances appropriately. Research undertaken by earlier researchers, such as those by Arofah (2019) reveals a beneficial influence of financial selfefficacy on financial management behavior.…”
Section: The Introductionmentioning
confidence: 96%